2002
DOI: 10.1021/jo010920f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Binding of Epimer A of the Covalent Hydrate of 6,7-Bis(trifluoromethyl)-8-d-ribityllumazine to a Recombinant F22W Bacillus subtilis Lumazine Synthase Mutant by 15N{19F} REDOR NMR

Abstract: The two epimeric covalent hydrates A and B of 6,7-bis(trifluoromethyl)-8-D-ribityllumazine are metabolically stable analogues of hypothetical intermediates proposed in the reactions catalyzed by riboflavin synthase and lumazine synthase. To confirm the stereochemical assignments previously based solely on results for epimer B, a (15)N[(19)F] REDOR NMR study was performed on the complex formed from epimer A and a recombinant, uniformly (15)N-labeled F22W mutant of Bacillus subtilis lumazine synthase. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The stereochemical assignments shown in Fig. 4 were suggested on basis of solid-state NMR studies [26,27]. …”
Section: Resultsmentioning
confidence: 99%
“…The stereochemical assignments shown in Fig. 4 were suggested on basis of solid-state NMR studies [26,27]. …”
Section: Resultsmentioning
confidence: 99%
“…However, only the epimer that bound to RS underwent a B. subtilis LS‐catalyzed fluoroform elimination to produce 7‐oxo compound 119 . Careful investigation of the epimer that did not undergo fluoroform elimination and corresponding 7‐oxo compound 119 by 15 N{ 19 F} REDOR NMR with the uniformly 15 N‐labeled 1‐MDa capsid of the B. subtilis LS F22W mutant demonstrated that the epimer that bound to RS was 117 , which established the configuration at C‐7 of corresponding intermediate 19 (Nu = OH) in the RS‐catalyzed reaction . These conclusions were later corroborated by 19 F NMR ligand perturbation studies with both 108 and 109 with B. subtilis LS.…”
Section: Nuclear Magnetic Resonance Studiesmentioning
confidence: 99%
“…In biological samples, even at low temperatures such as below )100°C, the molecular mobility gives rise to T 1 -relaxation times on the milliseconds time scale, thus significantly shorter than those of this investigation, but also than typical T 1 -relaxation times of 15 N, 13 C or 31 P in these systems. In 2 H-NMR experiments of biological samples fast recycle times of 100 ms-1 s are typically used, giving 2 H an advantage over 15 N, 13 C or 31 P. When considered as a whole, the integral intensity as measured in the 2 H detected RE-DOR experiment is comparable in sensitivity to 15 N.…”
Section: Applications To Biological Samplesmentioning
confidence: 99%
“…Their low sensitivity and small range of dipolar interactions, however, encouraged the use of the high-c nucleus 19 F as an alternative label with greatly enhanced sensitivity and range of measurable distances. Despite the structural modification it presents, it can be successfully employed in numerous biological applications [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In particular, pharmaceutical compounds (drugs) often contain fluorine, and 19 F-NMR is well suited to study the conformation of such compounds and ligand binding sites of proteins [2,13,16].…”
Section: Introductionmentioning
confidence: 99%